Innovating the treatment of COPD exacerbations: a phone interactive telesystem to increase COPD Action Plan adherence. Issue 1 (9th April 2019) - Farias, Raquel; Sedeno, Maria; Beaucage, Danielle; Drouin, Isabelle; Ouellet, Isabelle; Joubert, Alexandre; Abimaroun, Rita; Patel, Meena; Abou Rjeili, Mira; Bourbeau, Jean
Abstract : Introduction: Self-management interventions with Written Action Plans and case management support have been shown to improve outcomes in patients with chronic obstructive pulmonary disease (COPD). Novel telehealth technologies may improve self-management interventions. The objectives of this study were to determine whether the use of an interactive phone telesystem increases Action Plan adherence, improves exacerbation recovery and reduces healthcare use in a real-life practice of a COPD clinic. Methods: Initially, 40 patients were followed by a COPD telesystem for 1 year. Detailed data from patients' behaviours during exacerbations was recorded. The telesystem use was then extended to 256 patients from a real-life COPD clinic. Healthcare utilisation for the year before and after telesystem enrolment was then assessed through hospital administrative databases. Results: Thirty-three of the 40 patients completed the initial 1-year study. Eighty-one exacerbations were reported in the 1-year follow-up. Action Plan adherence was observed for 72% of the exacerbations and those who were adherent had a significantly faster exacerbation recovery time. The large-scale implementation of the telesystem resulted in a significant decrease in the proportion of patients with ≥1 respiratory-related emergency room (ER) visits (120 before vs 110 after enrolment, p<0.001) and with ≥1 COPD-related hospitalisations (75 before vs 65 after enrolment, p<0.001). Discussion: COPD Written Action Plan adherence was further enhanced with the use of telehealth technologies in a specialised clinic with experience in COPD self-management. Patients followed by the telesystem recovered faster from exacerbations and had a further decrease in COPD-related ER visits and hospitalisations. Trial registration number: NCT02275078 .